A comparison of three algorithms applied in thermal-hydraulics and neutronics codes coupling for lbe-cooled fast reactor. (15th December 2020) - Yang, Dongmei; Liu, Xiaojing; Zhang, Tengfei; Cheng, Xu
Highlights: The OSSI method, FPI method and ABN method have been implanted in the coupling process. The ABN method combines the advantages of JFNK method and OSSI method. The ABN method balances accuracy and computational cost in mild transients. Abstract: In this research, the Operator-Splitting semi-implicit (OSSI) method, fixed-point implicit (FPI) method and Approximate Block Newton (ABN) method have been applied to the coupling of thermal-hydraulics code COBRA and neutronics code SKETCH-N. In the OSSI method, there's only one data exchange within a time step. In the FPI coupling, an iteration convergence has been added to the OSSI coupling framework to ensure the coupling results converged. And in the ABN method, a variant of Jacobian-free Newton Krylov method has been applied, which removes the Jacobian matrix construction and storage. Three temporal schemes have been validated through a PWR control rod bank ejection benchmark to show their applicability. Moreover, a LBE-cooled fast reactor control rods withdrawal accident applying two time steps has been simulated. And the results indicate that the ABN method applied in the mild transient generally outperforms the other two methods in both the convergence speed and the computational cost.